2015
DOI: 10.1007/s00787-015-0683-7
|View full text |Cite
|
Sign up to set email alerts
|

Are all the 18 DSM-IV and DSM-5 criteria equally useful for diagnosing ADHD and predicting comorbid conduct problems?

Abstract: In view of ICD-11 revision, we evaluate whether the 18 DSM-IV diagnostic items retained by DSM-5 could be further improved (i) in predicting ADHD 'caseness' and 'impairment' and (ii) discriminating ADHD without CD (ADHD - CD) cases from ADHD with CD (ADHD + CD) cases. In a multi-centre study sample consisting of 1497 ADHD probands and 291 unaffected subjects, 18 diagnostic items were examined for redundancy; then each item was evaluated for association with caseness, impairment and CD status using Classical Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
2
11
1
Order By: Relevance
“…Regarding the possible implications for the review of ADHD symptomology, the symptoms “Loses things necessary for task or activities” on the IA scale and “Talks excessively” and “Blurts out answers before questions have been completed” on the HI scale present relatively low discrimination values than the other symptoms as well as poor information and the lowest reliability values of all of the levels for the respective latent traits. These results partially replicate previous findings revealing relatively low discriminative values for the symptoms “loses things” [ 5 , 8 , 22 , 26 , 29 ], “talks excessively” [ 5 , 8 , 22 , 24 ] and “blurts answers” [ 8 , 24 , 29 ]. Nevertheless, relatively high levels were maintained.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Regarding the possible implications for the review of ADHD symptomology, the symptoms “Loses things necessary for task or activities” on the IA scale and “Talks excessively” and “Blurts out answers before questions have been completed” on the HI scale present relatively low discrimination values than the other symptoms as well as poor information and the lowest reliability values of all of the levels for the respective latent traits. These results partially replicate previous findings revealing relatively low discriminative values for the symptoms “loses things” [ 5 , 8 , 22 , 26 , 29 ], “talks excessively” [ 5 , 8 , 22 , 24 ] and “blurts answers” [ 8 , 24 , 29 ]. Nevertheless, relatively high levels were maintained.…”
Section: Discussionsupporting
confidence: 89%
“…These findings also support the appropriateness of reducing the list of symptoms to just include those with greater discriminatory capacity, thereby resulting in a more parsimonious diagnostic process. Additionally, based on recent evidence showing that some symptoms do have more predictive power on both diagnosis and impairment level [ 29 ], our results suggest that reducing the scale without losing relevant information would allow it usage as a screening tool. Interestingly, previous studies reveal that certain symptoms (e.g.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Despite substantial evidence supporting the use of the bifactor model for ADHD symptoms, existing studies that used IRT set forward either a single unidimensional model for all ADHD symptoms, or separate unidimensional models for inattention and hyperactivity/impulsivity (Garcia-Rosales et al, 2015; Gomez, 2008; Li, Reise, Chronis-Tuscano, Mikami, & Lee, 2015; Purpura, Wilson, & Lonigan, 2010). While assumptions of unidimensionality of ADHD symptoms may be appropriate for nonclinical samples (Arias et al, 2016), the multidimensionality that is observed in clinical samples and associated unmodeled residual dependence between items may result in biased parameter estimates (Chen & Thissen, 1997), and overestimation of IRT item information and test reliability (Sireci, Thissen, & Wainer, 1991).…”
Section: Irt and Adhd Rating Scalesmentioning
confidence: 99%
“…An alternative novel approach is to view ADHD as a network of interacting symptoms, providing detailed information on the complex relations between symptoms. While all 18 of the DSM symptoms contribute significantly and independently to the disorder [7], given the heterogeneity of the ADHD presentation, identifying symptoms that are central to the disorder have multiple implications including better understanding aetiological factors associated with the disorder, increasing accuracy in predicting outcomes and informing treatment approaches.…”
Section: Introductionmentioning
confidence: 99%